GERAKAN SEHAT PEDULI LANSIA DI DESA JOGOROGO, JOGOROGO, NGAWI - Rooiqoh, Qothrunnadaa (PC IAI Sragen, 2025)
The elderly are individuals who have reached the age of 60 and above. This activity aims to provide health education and determine the results of nutritional status assessments, blood pressure checks, blood sugar levels, and uric acid levels in the elderly. The implementation method uses a descriptive educational approach with a qualitative approach. This activity was held on Friday, March 8, 2024, at the Jogorogo Village Hall, Jogorogo Ngawi District, with 26 participants. The results of this activity were the implementation of health checks, including nutritional status measurements, blood pressure checks, blood sugar and uric acid level checks, and the provision of material on the prevention of non-communicable diseases, as well as group exercises with the elderly. The evaluation of the activity showed that participants actively participated from start to finish, were engaged in discussions, and actively followed the guided exercises. Therefore, community service activities can serve as an alternative for early detection of NCDs among the elderly.